PENGARUH GAYA KEPEMIMPINAN DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA SERTA IMPLIKASINYA TERHADAP KINERJA KARYAWAN (Studi Kasus Pada Karyawan PT. EMSONIC Indonesia, Cibitung Jawa Barat) - Pudji Astuty; Dewi Zuniasih (Fakultas Ekonomi Universitas Borobudur, 2018)
This study aims to determine the extent of the influence of leadership styles, career development on employee performance through job satisfaction at PT. Emsonic Indonesia Cibitung West Java.The data used in this study in the form of primary data collected from respondents' answers based on questionnaires given, as many as 82 people. Data processing method uses Path Analysis method with the help of SPSS version 22.0. The statistical test used the significance test of individual parameters (t test) and simultaneous significance test (Test F).The results showed that simultaneously leadership style variables, career development and job satisfaction have a significant effect on employee performance. Partially shows that analysis 1: leadership style variables significantly affect employee performance, while analysis 2: career development variables significantly affect employee performance and on analysis 3: job satisfaction variable significantly affect employee performance. Keywords: leadership style, career development, job satisfaction and employee performance